2006
DOI: 10.1007/s00542-006-0231-y
|View full text |Cite
|
Sign up to set email alerts
|

Micro thermal design of swing arm type small form factor optical pick-up system

Abstract: New multimedia information environment requires smaller optical data storage systems. However, one of the difficulties in the design of small form factor (SFF) optical pick-up is to emit the heat which is usually generated from laser diode (LD). The generated heat may reduce the optical performance of the system as well as the lifetime of LD. Therefore, it is important to include the thermal consideration in the development of SFF optical pick-up system for the high performance and longer lifetime of LD. It is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2006
2006
2012
2012

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…As explained above, the actuator suspension has a form of laminated structure and each of the layers has the dimension as in Table 2. The initial pick-up mass is supposed as 29 mg considering previous pick-up examples (Lee et al 2006). By the finite element (FE) analysis, the initial design is confirmed to have 15.8 kHz torsional frequency and the DC-sensitivity for focusing as 0.328 mm/V; both satisfy the design requirements.…”
Section: Design Requirementsmentioning
confidence: 98%
See 1 more Smart Citation
“…As explained above, the actuator suspension has a form of laminated structure and each of the layers has the dimension as in Table 2. The initial pick-up mass is supposed as 29 mg considering previous pick-up examples (Lee et al 2006). By the finite element (FE) analysis, the initial design is confirmed to have 15.8 kHz torsional frequency and the DC-sensitivity for focusing as 0.328 mm/V; both satisfy the design requirements.…”
Section: Design Requirementsmentioning
confidence: 98%
“…Furthermore, the heat transfer of hard disk drive (HDD) rotating disk is researched by Cho et al (2003). Recently, Lee et al (2006) suggested a micro thermal design of a swing arm type SFF optical pick up system; however, the design is only concerned about the thermal characteristics from heat emission from optical pick up unit without dynamic consideration and the convection coefficient is assumed without verifications.…”
Section: Introductionmentioning
confidence: 99%